MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION TERHADAP KEMAMPUAN PEMECAHAN MASALAH BAHASA INGGRIS - John Andreas Laia (Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to determine: the effect Auditory Intellectually Repetition the problem solving ability students' English learning SMP Negeri 2 Mazino the academic year 2021/2022. The research method used an experimental research method with the research design used the researcher quasi-experimental design, none Quivalent control group design. The research sample is the students SMP Negeri 2 Mazino VIII-a with total 28 as the experimental class and class VIII-b with total 34 the control class. The results the study: (1) the average student learning outcomes the experimental class were 81.3 with good classification and the average student learning outcomes the control class were 56.3; (2) Based on the final test data processing, was obtained that tcount was 10,575 and ttable 2,000 and when compared, tcount > ttable, it means that there effect of Auditory Intellectually Repetition on English problem solving ability in class VIII semester 1 Mazino 2 Junior High School.